Public Intention on Bandung Tour on Bus - Tezza Adriansyah Anwar; Yessy Puspita (Journal of Information Technology, 2020)
Bandung is known as the capital of West Java. Bandung also develops as a culinary city. As a form of the Government's responsibility to facilitate tourists who come to Bandung, the Government has officially announced the "Bandros" Tourism Bus (Bandung Tour on Bus). But practically, there are many problems faced by stakeholders. Standardization of prices among passengers, limits on the number of buses that cannot serve passengers, unclear routes including departures and arrivals, unhealthy management for safety factors and an increase in the number of passengers that have a negative impact due to the quality of service. The purpose of this study is to describe service quality, community satisfaction and community interest in reusing Bandros, and also to obtain the results of an analysis of the extent to which service quality affects community satisfaction and its impact on community interest in reusing Bus Bandros. In this study, researchers used the descriptive-verification method. This method is used to verify the quality of service perception, community satisfaction and community intentions to reuse Bus Bandros by involving 500 respondents who wish to use Bus Bandros. The distribution and selection of respondents was carried out using convenience sampling. Path analysis is also used in this study. Based on the results of the statistical testing process found significant perceptions between service quality variables and brand image with public interest in the city of Bandung to use Bus Bandros. For recommendations in this study, clarity of information can increase the public's intention to use Bus Bandros, because the information submitted will provide clarity in order to increase public intention to ride Bus Bandros.